A manifesto for a globally diverse, equitable, and inclusive open science - Sakshi Ghai; Rémi Thériault; Patrick Forscher; Yuichi Shoda; Moin Syed; Arathy Puthillam; Hu Chuan Peng; Dana Basnight-Brown; Asifa Majid; Flavio Azevedo; Leher Singh (Communications Psychology)
Abstract The field of psychology has rapidly transformed its open science practices in recent years. Yet there has been limited progress in integrating principles of diversity, equity and inclusion. In this Perspective, we raise the spectre of Questionable Generalisability Practices and the issue of MASKing (Making Assumptions based on Skewed Knowledge), calling for more responsible practices in generalising study findings and co-authorship to promote global equity in knowledge production. To drive change, researchers must target all four key components of the research process: design, reporting, generalisation, and evaluation. Additionally, macro-level geopolitical factors must be considered to move towards a robust behavioural science that is truly inclusive, representing the voices and experiences of the majority world (i.e., low-and-middle-income countries).